2019
DOI: 10.2174/1871526518666180530075523
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Infection During Pregnancy: The Overlooked Cause of Maternal and Fetal Mortality

Abstract: Hepatitis E virus (HEV) is one the leading causes of maternal and fetal mortality. Nevertheless, in some geographical locations, especially Egypt, despite having high frequency of HEV seropositivity, HEV infection follows an asymptomatic or mild course during pregnancy. These anomalous observations have distracted attention from the importance of HEV infection in pregnant women. While tragic cases of HEV-infected pregnant women cannot be neglected any longer. These circumstances create a strong demand for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Hepatitis E virus (HEV) is a singlestrand RNA virus that in humans causes an acute viral hepatitis after an incubation period of 4-5 weeks, but the infection is often asymptomatic. However, even if the mortality rate is generally low (0.5%), it can reach 25% in pregnant women (Farshadpour et al, 2018). HEV is divided in into eight recognized genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis E virus (HEV) is a singlestrand RNA virus that in humans causes an acute viral hepatitis after an incubation period of 4-5 weeks, but the infection is often asymptomatic. However, even if the mortality rate is generally low (0.5%), it can reach 25% in pregnant women (Farshadpour et al, 2018). HEV is divided in into eight recognized genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…HEV infection is one of the leading causes of fetal and maternal death. 54 In pregnant women with HEV infection, cytokine gene polymorphisms are associated with adverse pregnancy outcomes. 55 During the second and third trimester of pregnancy, HEV infection leads to hepatic failure and increases the risk of mortality 30% to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…96 HEV has also remained one of the main factors in causing maternal and fetal mortality during pregnancy, and around 15–60% of acute hepatitis E infection progresses to acute liver failure in pregnant patients in developing countries. 97 , 98 In Iran, epidemiological studies have reported seropositivity between 3.6 to 7.4% amongst pregnant women, depending upon the geographical location and the level of hygiene in each area. 99 …”
Section: Hepatitis E (Hev)mentioning
confidence: 99%